Materials composed of the Drosophila Hox protein Ultrabithorax are biocompatible and nonimmunogenic. Issue 4 (8th August 2014) - Patterson, Jan L.; Arenas‐Gamboa, Angela M.; Wang, Ting‐Yi; Hsiao, Hao‐Ching; Howell, David W.; Pellois, Jean‐Philippe; Rice‐Ficht, Allison; Bondos, Sarah E.
Abstract Although the in vivo function of the Drosophila melanogaster Hox protein Ultrabithorax (Ubx) is to regulate transcription, in vitro Ubx hierarchically self‐assembles to form nanoscale to macroscale materials. The morphology, mechanical properties, and functionality (via protein chimeras) of Ubx materials are all easily engineered. Ubx materials are also compatible with cells in culture. These properties make Ubx attractive as a potential tissue engineering scaffold, but to be used as such they must be biocompatible and nonimmunogenic. In this study, we assess whether Ubx materials are suitable for in vivo applications. When implanted into mice, Ubx fibers attracted few immune cells to the implant area. Sera from mice implanted with Ubx contain little to no antibodies capable of recognizing Ubx. Furthermore, Ubx fibers cultured with macrophages in vitro did not lyse or activate the macrophages, as measured by TNF‐α and NO secretion. Finally, Ubx fibers do not cause hemolysis when incubated with human red blood cells. The minimal effects observed are comparable with those induced by biomaterials used successfully in vivo. We conclude Ubx materials are biocompatible and nonimmunogenic. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1546–1553, 2015.